Effects of Multicomponent Exercise Training on the Health of Older Women with Osteoporosis: A Systematic Review and Meta-Analysis - Linhares, Diego Gama; Borba-Pinheiro, Claudio Joaquim; Castro, Juliana Brandão Pinto de; Santos, Andressa Oliveira Barros dos; Santos, Luciano Lima dos; Cordeiro, Lilliany de Souza; Drigo, Alexandre Janotta [UNESP]; Nunes, Rodolfo de Alkmim Moreira; Vale, Rodrigo Gomes de Souza (MDPI, 2022)
This study aimed to analyze the effects of multicomponent exercise training in older women with osteoporosis. We conducted a systematic review following the PRISMA guidelines and registered on PROSPERO (number CRD42022331137). We searched MEDLINE (via PubMed), Web of Science, Scopus, and CINHAL databases for randomized experimental trials that analyzed the effects of physical exercise on health-related variables in older women with osteoporosis. The risk of bias in the studies was verified using the Cochrane Collaboration tool and the Jadad scale was used to assess the methodological quality of the studies. Fourteen randomized controlled trials were included, with a total of 544 participants in the experimental group and 495 in the control group. The mean age of all participants was 68.4 years. The studies combined two to four different exercise types, including strength, aerobic, balance, flexibility, and/or functional fitness training. The practice of multicomponent training with an average of 27.2 weeks, 2.6 sessions per week, and 45 min per session showed improvements in strength, flexibility, quality of life, bone mineral density, balance, and functional fitness and reduced the risk of falls in older women with osteoporosis. Multicomponent training was shown to be effective in improving health-related variables in older women with osteoporosis.
Keywords: bone density; elderly; exercise; health; muscle strength; osteoporosis; physical functional performance; postural balance; quality of life; resistance training